The Photoshop CS3 book for digital photographers - Kelby, Scott (Voices that matter., 2007)
A step-by-step handbook takes readers through the fundamental principles and techniques of the digital photography editing process using Adobe Photoshop CS3, covering everything from color correction and digital body-sculpting to organization and output.